Place As An Extended Technique: The Quarantine Concerts & New Experiential Music Platforms - Zucker, Ben (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
In this piece, Ben Zucker profiles Chicago’s Experimental Sound Studio and its decision to move online with a series of livestreamed performances known as The Quarantine Concerts (TQC). He examines the meaning of “place” for virtual gatherings such as TQC, and discusses how musicians have had to rethink what liveness means and how it is practiced under the new constraints.